Two New Species of Ochotona (Mammalia, Lagomorpha) From Xizang, China - Xuan Pan; Xuming Wang; Robert W. Murphy; Buqing Peng; Zongyun Zhang; Rui Liao; Shunde Chen; Shaoying Liu (Ecology and Evolution)
ABSTRACT During small mammal faunal surveys conducted in the Xizang Autonomous Region, China, in 2003, 2023, and 2024, we collected two previously unidentifiable taxa of pikas (Ochotona). Phylogenetic analyses based on both mitochondrial and nuclear gene sequences resolved these specimens as distinct lineages within the O. macrotis and O. forresti species groups, both in the subgenus Conothoa. Morphological comparisons further supported their uniqueness. Consequently, we described them here as two new species. One new species, O. galunglaensis sp. nov., collected from Motuo and Bomi counties, exhibits the following diagnostic characteristics: (1) diminutive body size (mean head‐body length < 150 mm); (2) reduced auricular dimensions (ear length < 18 mm); (3) summer pelage exhibits brown‐red on top of head, beneath eyes, and shoulders; neck bears a gray patch and ventral light brown‐gray; (4) without oval foramen; foramina incisivum narrow and palatal foramina merged; and (5) premaxillae on both sides of foramina incisivum have a tendency to close in some specimens. The other new species, O. legbona sp. nov., collected from Cuona county, is unique as follows: (1) comparable head‐body length to O. macrotis, but with much shorter ears (mean 23 mm vs. 31–35 mm in congeners); (2) characteristic black vibrissae lining the inner pinnae; (3) summer pelage exhibits brown‐red on head, shoulder, and neck; ventral brown‐yellow; and (4) without oval foramen; foramina incisivum narrow and palatal foramina merged. Our findings highlight the previously underestimated diversity within Conothoa and contribute to a more comprehensive understanding of pika diversity in the Himalayan region.